A hyphenated SMPS–ICPMS coupling setup: Size-resolved element specific analysis of airborne nanoparticles. (October 2015) - Hess, Adrian; Tarik, Mohamed; Ludwig, Christian
Abstract: Physical and chemical characterization of gas borne particles in the nanometer to sub‐micrometer size range includes knowledge about particle size distribution and chemical composition, possibly with a high time resolution. However, most of the available techniques are offline methods and/or not able to provide such physical and chemical information simultaneously. Scanning Mobility Particle Sizer (SMPS) is a well-established and widely used technique for determining size distribution and number concentration of such particles, within scan durations of a few minutes. Inductively Coupled Plasma Mass Spectrometry (ICPMS) is a highly sensitive multi-element technique, allowing the determination of elemental composition with excellent detection limits and a wide dynamic concentration range. In this work, SMPS and ICPMS were coupled to one hyphenated system which allows achieving on-line and simultaneously size and chemical information with SMPS-typical time resolutions. A Rotating Disk Diluter was used as sample introduction interface, and the SMPS flow concept was re-designed to fulfill the requirements of both different analytical methods. The developed setup was successfully tested with a model aerosol containing airborne silver nanoparticles. Proper SMPS operation under argon atmosphere instead of air was validated. The presented setup was applied to scan the particle size range from 7 to 156 nm within 120 s. Similar sensitivities and efficiencies compared to that of state-of-the-art SMPS and ICPMS instruments were achieved. Graphical abstract: Highlights: SMPS–ICPMS setup with Rotating Disk Diluter as sample introduction interface. Size resolved concentration and element information on aerosol nanoparticles. Independent of source aerosol flow rate: suitable for real-sample investigation. Detailed description of instrumental setup and operating parameters. Instrument operation demonstrated on a simple model aerosol.